EFFECT OF PEER EDUCATION MODEL ON KNOWLEDGE AND SELF-EFFICACY OF CHILDREN IN THE PREVENTION OF PHYSICAL SEXUAL VIOLENCE - Rufaida Nur Fitriana; Chriswardani Suryawati; Zubaidah Zubaidah (Belitung Nursing Journal, 2018)
Background: The rate of incidence of physical assault on school children increases from year to year. Efforts to prevent child sexual violence can be done through school-based education with student empowerment. Objective: To identify the effect of education by peers on the knowledge and self-efficacy of primary school children in preventing sexual violence in Grabag sub-district, Magelang regency, Indonesia. Methods: This study was a quasi-experimental study with pretest and posttest non-equivalent control groups. A total of 84 school-aged children were purposively recruited from two different primary schools. Each group consisted of 42 respondents. Children's Knowledge of Abuse Questionnaire-Revised III (CKAQ-RIII) instrument was used to measure knowledge and self-efficacy questionnaire was measured for self-efficacy. Data were analyzed using Wilcoxon and Chi-Square test. Results: The study showed that a statistically significant difference in the variables of both knowledge (p=0.008) and self-efficacy (p=0.000) in the intervention group after given peer education treatment. Conclusion: Educational interventions by peers can improve the knowledge and self-efficacy of primary school-aged children in preventing sexual violence. Peer education can be used as an effort to prevent sexual violence in children through school empowerment programs.